Formation control of multiple autonomous vehicle systems - Liu, Hugh H. T.; Zhu, Bo (Mechanical engineer) (Wiley, 2018)
"Presents representative case studies in selected applications in space, aerial, and robotic systems domains. - Introduces an experimental platform of using laboratory three-degree-of-freedom helicopters with step by step instructions as an example and exercises throughout the book for illustration purposes. - Open Source example models and simulation codes will be provided Marketing description- Primary: Researchers and academics in robotics and unmanned systems looking at formation problems. These include mechanical engineers, aerospace engineers and electrical engineers. Graduate students in Control within ME, EE, and AE are also a target as a supplemental publication. Secondary: Industry engineers developing guidance systems for formation control systems and graduate students in mechanical, electrical, and aerospace engineering"--